Augmentation of Nanofluids Heat transfer in a Circular Tube with Baffled Winged Twisted Swirl Generator - Salman, Sami D.; Abd Alsaheb, Ramzi Ata (Al-Khwarizmi Engineering Journal, 2018)
This article introduces a numerical study on heat exchange and corrosion coefficients of Zinc–water nanofluid stream in a circular tube fitted with swirl generator utilizing CFD emulation. Different forms of swirl generator which have the following properties of plain twisted tape (PTT) and baffle wings twisted tape (BTT) embeds with various ratio of twisting (y = 2.93, 3.91 and 4.89), baffle inclination angles (β = 0°, - 30° and 30) joined with 1%, 1.5% and 2% volume fraction of ZnO nanofluid were utilized for simulation. The results demonstrated that the heat and friction coefficients conducted by these two forms of vortex generator raised with Reynolds number, twist ratio and baffle inclination angles decreases. Likewise, the results showed that the heat transfer rate raised with accretion of ZnO nanoparticle concentration. Furthermore, the maximum rate of heat transfer with significant intension in friction coefficient has been produced by baffle wings tape with ratio of twisting y=2.93 and baffle angle β= -30 with 2% volume fraction of ZnO nanofluid.